OPTIMALISASI PROYEK INSTALASI GAS MEDIS DENGAN MENGGUNAKAN CRITICAL PATH METHOD (CPM) DAN PROGRAM EVALUATION AND REVIEW TECHNIQUE (PERT) DI RSIA ASIH JAKARTA SELATAN - Putra Lamjaya; Florida Butarbutar (Fakultas Teknik Unkris Jakarta, 2022)
Project scheduling is one of the elements of planning results that can provide information about the planned schedule and project progress in terms of resource performance in the form of costs, labor, equipment and materials as well as project duration plans with time progress to complete the required project. One method that is often used in scheduling and time and cost efficiency methods is CPM and PERT. The purpose of this research is to schedule the implementation and control of the medical gas installation project at RSIA ASIH to be more optimal. CPM is basically known as a critical path, namely a path in a network that has a series of activity components, with the longest total time and shows the fastest project completion time. The PERT method is a network-based project scheduling method that requires three time estimates for each activity, namely optimistic time, pessimistic time and realistic time. This research consists of 17 activities where the total time needed to work on this project is 33 weeks. By applying the CPM and PERT methods, the total time required is 30 weeks, so the processing time is 3 weeks more efficient. This can also reduce the costs needed in project work, where the total initial project cost required is . Rp1.165.500.000 to Rp 936.846.660 so that the work on this project will save Rp 228.653.340